Diagnostic yield of push-type enteroscopy in relation to indication. Issue 3 (1st March 1998) - Landi, B; Tkoub, M; Gaudric, M; Guimbaud, R; Cervoni, J P; Chaussade, S; Couturier, D; Barbier, J P; Cellier, C
Abstract : Background —Push-type enteroscopy, a recent method for investigating the small intestine, is currently undergoing assessment. Its diagnostic yield varies in the studies reported to date. Aim —To assess the diagnostic value of push-type enteroscopy according to indication. Patients and methods —From January 1994 to September 1995, 152 consecutive patients (mean age 34 years) underwent push-type enteroscopy (jejunoscopy, n=93; retrograde ileoscopy, n=17; and double way enteroscopy, n=42). The indications were: unexplained iron deficiency anaemia or macroscopic gastrointestinal bleeding (n=76), radiological abnormalities of the small intestine (n=23), chronic diarrhoea and/or malabsorption syndrome (n=18), abdominal pain (n=12), and miscellaneous (n=23). All patients had undergone previous negative aetiological investigations. Results —The jejunum and ileum were explored through 120 cm (30–160 cm) and 60 cm (20–120 cm). Digestive bleeding: lesions of the small bowel were found in 6% of the patients with isolated iron deficiency anaemia and 20% of patients with patent digestive haemorrhage. Radiological abnormalities of the small intestine: push-type enteroscopy provided a diagnosis or modified the interpretation of radiological findings in 18/23 cases (78%). Chronic diarrhoea and/or malabsorption: push-type enteroscopy yielded explanatory findings in four cases (22%). Abdominal pain: push-type enteroscopy provided no diagnosis. Conclusion —In this series, push-type enteroscopy was of particular value in investigating patients with radiological abnormalities of the small intestine. It was of some value in the exploration of patent digestive haemorrhage or chronic diarrhoea, but not of abdominal pain. Its value was limited in the exploration of iron deficiency anaemia.